Debt Accumulation in the CIS-7 Countries : Bad Luck, Bad Policies, or Bad Advice? - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2004)
Following the breakup of the Soviet Union in 1992, several low-income countries in the Commonwealth of Independent States (CIS) accumulated substantial external debt in a short time span, about half of which is owed to multilateral financial institutions. Three factors contributed to the current debt burden. First, the initial years of transition brought large systemic economic disruptions, loss of transfers from the center and collapse of trade relations among Council for Mutual Economic Assistance (CMEA) countries, and negative terms of trade shocks. Second, fiscal and other reforms, and consequently, growth revival, took longer than expected. Third, overoptimism by multilaterals contributed to the high debt levels. If external financial assistance, which was needed because of high social costs of the transition, had come in the form of grants in the first two or three years of the transition, the debt burden would have been lower and sustainable.